Explicit Learning of Arbitrary and Non-Arbitrary Action–Effect Relations in Adults and 4-Year-Olds - Verschoor, Stephan Alexander; Eenshuistra, Rena; Kray, Jutta; Biro, Szilvia; Hommel, Bernhard (Frontiers in Psychology, 2012)
Ideomotor theories claim that carrying out a movement that produces a perceivable effect creates a bidirectional association between the two, which can be used by action control processes to retrieve the associated action by anticipating its outcome. Indeed, previous implicit-learning studies have shown that practice renders novel but action-contingent stimuli effective retrieval cues of the action they used to follow, suggesting that experiencing sequences of actions and effects creates bidirectional action-effect associations. We investigated whether action-effect associations are also acquired under explicit-learning conditions and whether familiar action-effect relations (such as between a trumpet and a trumpet sound) are learned the same way as novel, arbitrary relations are. We also investigated whether these factors affect adults and 4-year-old children equally. Our findings suggest that explicit learning produces the same bidirectional action-effect associations as implicit learning does, that non-arbitrary relations improve performance without affecting learning per se, and that adults and young children show equivalent performance—apart from the common observation that children have greater difficulty to withstand stimulus-induced action tendencies.